Pelaksanaan One Student Saves One Family (Ossof) pada Keluarga dengan Salah Satu Anggota Keluarga Mengalami Hipertensi pada Era Pandemi Covid 19 - Olfah, Yustiana; Habsari , Kurniatin Nur; Sari, Anisa Kartika; Siswati, Tri (JOURNAL OF PHILANTHROPY: The Journal of Community Service, 2023)
Hypertension is a non-communicable disease characterized by an increase in blood pressure above normal limits. The prevalence of hypertension in Indonesia is always increasing from year to year. OSSOF-based Community Service activities aim to provide practical experience for students to learn to deal with health problems in the community. This activity was carried out for the family of Mr. A who is in the village of Guwosari, Pajangan, Bantul, Yogyakarta with hypertension problems in Mrs. A. The method applied is to provide hypertension education and teach hypertension exercises, health consultations, blood pressure checks and monitoring medication adherence. The results of the activity showed that the patient's knowledge about hypertension, complications of the disease, and diet in hypertensive patients increased and the patient was able to do hypertension exercise. In addition, monitoring medication adherence to families increases patient compliance. Patients and family members stated that they would be committed to supporting the care and treatment of Mrs. A . This shows that this activity is able to have a positive impact, especially for the family of Mrs.A.